Georgia Architectural and Historic Properties Survey of 408 West St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 408 West St., Valdosta, Ga., December 1980. 1 story small rectangular shiplap sided house with tin gabled roof and exposed rafters. Exterior chimney. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: App. 1920. Typical house in densely populated area settled by middle to low income. Significant as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 408 West St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.0 MB (85,027,873 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)